2018
DOI: 10.1556/2060.105.2018.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Surface electromyographic evaluation of the neuromuscular activation of the inspiratory muscles during progressively increased inspiratory flow under inspiratory-resistive loading

Abstract: This study aimed to evaluate neuromuscular activation in the scalene and sternocleidomastoid muscles using surface electromyography (EMG) during progressively increased inspiratory flow, produced by increasing the respiratory rate under inspiratory-resistive loading using a mask ventilator. Moreover, we attempted to identify the EMG inflection point (EMG) on the graph, at which the root mean square (RMS) of the EMG signal values of the inspiratory muscles against the inspiratory flow velocity acceleration abru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Figure 6 plots the EEG-sEMG coherence waveforms for three factors in various bands of the C3 and biceps channels in vertical motion. It can be observed that the frequency bands in which the coefficient values increase significantly are concentrated at [16][17][18][19][20][21][22][23][24][25] Hz. It has coherence in the local frequency band above 25 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 plots the EEG-sEMG coherence waveforms for three factors in various bands of the C3 and biceps channels in vertical motion. It can be observed that the frequency bands in which the coefficient values increase significantly are concentrated at [16][17][18][19][20][21][22][23][24][25] Hz. It has coherence in the local frequency band above 25 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…Root mean square (RMS) is a relatively common sEMG signal time-domain feature, and to a certain extent, reflects the contribution of each muscle group in the process of motion. RMS is defined as [18]:…”
Section: Feature Extractionmentioning
confidence: 99%
“…Conflict of interest: None declared. The column P SC rest depicts the rest and P SC bump the P AV value during the "bump" period in the sternocleidomastoid (SCM) region, while similarly P D rest is the rest and P D bump is the "bump" value of P AV in the diaphragm (DIA) region, according to the labeling by the Japanese group [31]; the P AV influx in percentages for the SCM and the DIA regions are denoted by ΔP SC and ΔP D , respectively; the maximum influx for each volunteer is given in the following column, depicted as ΔP MAX ; T RLX is the relaxation period in milliseconds after the P AV was returned to the values equal to the initial state; the raw AVG shows the simple average value for all columns, while SD shows the standard deviation for the last four columns on the right; the most important values in the first (No. ), sixth (ΔP SC ) and seventh (ΔP D ) columns are in bold; while Δ MIN shows the minimal increase, Δ MAX shows the maximum increase for the last two columns on the right.…”
Section: Acknowledgmentmentioning
confidence: 99%